Proteomics identifies new potential therapeutic targets of diabetic retinopathy. Issue 4 (1st April 2022) - Zhou, Huanran; Xu, Qian; Li, Hongxue; Hu, Yuxin; Kuang, Hongyu
ABSTRACT: Retinal pigment epithelium (RPE) is an important component of the outer blood-retinal barrier and plays a critical role in maintaining retinal homeostasis. Alterations in RPE can be detected during the early stages of diabetic retinopathy (DR). However, the molecular mechanisms underlying these early changes remain unclear. We investigated the molecular changes induced in the RPE by high glucose concentrations by constructing a high glucose-induced ARPE-19 cell injury model simulating the DR environment in vitro . Proteomic analysis was conducted to measure differences in protein expression between cells treated with normal (5 mM) and high (25 mM) glucose concentrations, and bioinformatics techniques were used to analyze the mechanism of action. The results of the proteomic analyses were validated using western blotting. High glucose levels inhibited the proliferation of ARPE-19 cells. We identified 88 upregulated proteins and 114 downregulated proteins. Six of these proteins were selected for further validation. Changes in the proteome mainly affected the lysosome and cell cycle pathways. Proteomic differences between ARPE-19 cells treated with normal and high glucose concentrations indicate that damage to the RPE in DR may be caused by specific mechanisms. Our study verified protein changes in ARPE-19 cells in a high-glucose environment and may provide new strategies for understanding the molecular mechanisms underlying DR. Graphical abstract: uf0001